A review of the analysis of ground reaction force among adults with lower limb problems - Deepashini Harithasan,; Nur Aqilah Abd Razak, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The ground reaction force (GRF) is the equal opposing load transfer from the body to the ground, also called vertical load transfer. The GRF would produce stress waves transmitted toward the lower extremities during the heel strike of a gait cycle. Too much force imposed on the lower extremities for an extended period will cause harmful effects such as injuries or alterations in gait. This article presents a review of the literature on GRF analysis among adults with lower limb problems where comparisons between healthy and unhealthy subjects were analyzed, focusing on the compensation in each lower limb. A literature search of published articles in Science Direct and PubMed databases from August 2015 to March 2021 was analyzed. The keywords used for the search were (plantar force OR vertical load transfer OR ground reaction force) AND (lower limb OR lower extremities OR leg OR foot) AND (impairment OR problem OR injury). The literature search identified 22 relevant studies which were screened independently by two reviewers. Lower limb problems such as unilateral transfemoral amputation, unilateral transtibial amputation, patellofemoral pain, anterior cruciate ligament injury, knee arthroplasty, knee osteoarthritis, diabetic foot, total hip replacement, pronated foot proved to alter the GRF significantly. Patients used to shift their weight on the opposite leg as compensation, which acts as a pain-free mechanism. This paper has provided sufficient understanding regarding GRF among adults with lower limb problems. The knowledge concerning compensation may help physical therapists implement the appropriate intervention for patients with lower limb problems.